THE CREATION OF PATTERN OF MAIN CHARACTERS OF WAYANG BEBER FOR DESIGNING OF THE ICONOF PACITAN AS CITY OF TOURISM - Agus Ahmadi; Sumadi Sumadi; Fitri Murfianti; Sri Murwanti (Proceeding of International Conference on Art, Language, and Culture, 2019)
Wayang beber is both of a of fine artwork and wayang/puppet show art. In this paper wayang beber is discussed from the point of view of art or craft art in making patterns as designs or references for the realization of works of art with several techniques to adjust the main ingredients. Wayang beber as the original traditional art of Pacitan which contains local wisdom that needs to be conservation efforts, research, creation and innovation.This effort is being done to make  wayang beber is suitable to be used as a source of ideas in the creation of the icon or logo of the Pacitan as a city of tourism. The process of creating this work through stages: problem identification, planning, drawing design, testing and implementation. The results of this drafting were aimed at improving, preserving Pacitan Wayang Beber, which is useful and widely known to the public. This paper is a part of the description of this Art Creation Research with the theme of design or design of tourist icons, through relief designs and sculptures, monument designs / monuments, city garden decoration works, with ideas of form, main characters, ornaments, arrangement patterns, stories and meanings Original Pacitan Wayang Beber. This description describes a part of the creation process in choosing the wayang beber scene, determining the main character, refining the shape and costume of the chosen figure to create a creative, innovative and meaningful Pacitan City Tourism Icon design. The relief works will be made using brass or copper plates. Ikon Pacitan's work can be done for the interior but is more appropriate for the exterior. Based on the identification of the selected wayang beber, the main characters of wayang beber Pacitan namely Dewi Sekartaji, Raden Panji, Naladerma and Tawangalun, were also found ornaments of various motifs of plants typical of Pacitan Wayang Beber. This main character is used as the main subject in the tourist icon design. The Pacitan City Tourism icon / logo is a new creation of wayang Beber combined with the form of gunungan wayang kulit and supplementary decorative motifs. The pattern resulted, is a relief. It was made of brass plate with carving technique and decorated with the technique of sunggingan or coloring by acrylic paint.